2009
DOI: 10.1038/ajg.2009.121
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Decreases Diverticular Complications

Abstract: Objectives Little is known about the effect of physical activity on diverticular complications. This study examined prospectively the association between physical activity and diverticular bleeding and diverticulitis. Methods We studied 47,230 US males in the Health Professionals Follow-up Study cohort who were aged 40–75 years and free of diverticular disease, gastrointestinal cancer and inflammatory bowel disease at baseline in 1986. Men reporting newly diagnosed diverticular disease on biennial follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
106
1
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(116 citation statements)
references
References 44 publications
1
106
1
8
Order By: Relevance
“…Smoking and obesity are known to increase the incidence of diverticulitis and complicated diverticulitis [24][25][26][27] ; in contrast physical activity prevents diverticulitis and reduces the risk of complicated diverticulitis. 28,29 The effects of nutrition habits on diverticulitis are controversial. [30][31][32] In contrast to lifestyle changes, operative therapies for diverticulitis seem effective because they are independent of patients' compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking and obesity are known to increase the incidence of diverticulitis and complicated diverticulitis [24][25][26][27] ; in contrast physical activity prevents diverticulitis and reduces the risk of complicated diverticulitis. 28,29 The effects of nutrition habits on diverticulitis are controversial. [30][31][32] In contrast to lifestyle changes, operative therapies for diverticulitis seem effective because they are independent of patients' compliance.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established from large-population studies and meta-analyses that there is an inverse relationship between physical activity and the incidences of colorectal carcinoma, cancer, and diverticulitis 24,25) . Conversely, gastrointestinal symptoms are a well-known downside of exercise.…”
Section: Effect Of Food Ingestion On the Gastrointestinal Tract At Rementioning
confidence: 99%
“…Further evidence comes from the American Healthcare Professionals Cohort Study, which reported a 1.78-fold (95% CI 1.08–2.94) increase in the risk of acute diverticulitis with obesity [17]. This link with obesity was also suggested by a 25% decrease in the risk of diverticulitis in those in this cohort who undertook vigorous physical activity compared to those that did not [18]. Reported associations of an increased risk of acute diverticulitis include use of aspirin, non-steroidal anti-inflammatory agents and alcohol [19,20].…”
Section: Occurrencementioning
confidence: 99%